Measuring quality of hepatitis B care in a remote Australian Aboriginal community: opportunities for improvement. Issue 8 (31st May 2022) - Narayana, Sumudu; Nugent, Michael; Woodman, Richard; Larkin, Michael; Ramachandran, Jeyamani; Muller, Kate; Wigg, Alan
Abstract: Background: Chronic hepatitis B (CHB) infection remains a significant public health issue for Indigenous Australians, in particular for remote communities. Aim: To evaluate the spectrum of hepatitis B virus (HBV) care provided to a remote Aboriginal community. Measures studied included screening, seroprevalence, vaccination rates and efficacy, and HCC risk and surveillance adherence. Methods: A retrospective audit of HBV care received by all permanent residents currently attending a remote Aboriginal Health service. This study was endorsed by both the local Aboriginal Health service and the Aboriginal Health Council of South Australia. Results: A total of 208 patients attended the clinic, of whom 52% (109) were screened for HBV. Of these, 12% (13) had CHB and 20% (22) had evidence of past infection. Similarly, of the 208 attending patients, complete vaccination was documented in 48% (99). Of the 33 patients with post‐vaccination serology, 24% (8) had subtherapeutic (<10 IU/mL) levels of HBsAb. Subtherapeutic HBsAb was independently associated with higher Charlson Comorbidity scores (odds ratio = 17.1; 95% confidence interval 1.2–243.3; P = 0.036). Definitive breakthrough infection was identified in 6% (2) patients. One HBsAg positive patient was identified as needing HCC surveillance, but had not undertaken HCC surveillance. Conclusion: Opportunities to improve the quality of CHB care through increased HBV vaccination, screening and adherence to HCC surveillance were identified. High rates of subtherapeutic vaccine responses and documented breakthrough infection raises concerns about the effectiveness of current CHB vaccines in this population.